Nos 250 anos da região demarcada do Douro : da companhia pombalina à regulação interprofissional - Pereira, Gaspar Martins (2008)
As we celebrate the 250 years of the Demarcated Region of the Douro, whose creation was determined by the royal charter of 10 September 1756, we believe to be important to try and understand not only the relevance of such ground-breaking measure in the international winegrowing context, which anticipated many aspects of the modern concept of denomination of controlled origin, but also its framing in the long history of the winegrowing region of the Douro, creating, simultaneously, a lasting vector of identity and regional unit in a territory extremely divided from and administrative standpoint.